Engineering Fette320 - Pratama, Stephen; Hutahaean, Hotma Antoni (Metris: Jurnal Sains dan Teknologi, 2017)
This Research in intended the Effect of manufactures electrical wiring low voltage. A problem that often occurs on the floor of the factory is the production of a quality mismatch on the cable NYM 2 x 1.5 mm2 will cause the occurrence of reduced demand from consumers and would harm consumers when menggunakanya. Bad results on the wire can not disconnect from the production process because the engine is one of the very important factor who fought in the quality of the wiring in the produce. As a result, the value of the isoaltor and the koduktor a cable can be a good or a bad fit with the existing machine settings. Usually many companies understand the appropriate combination in getting optimal results from the machine in karenakan costs incurred to figure it out pretty expensive. This would result in losses for the company in an amount large enough because the company would have difficulty fulfilling customer requests. For the optimal settings for analysis identifying the cable NYM using taguchi methods, alphabets experiment design and response Surface so that it can be done the calculation of total to quality cable compared with waste that should be the responsibility of the company due to the cable does not meet the specifications in the set (SNI). To conduct the process of identifying the need to know the data cable-owned waste terytama on cable cable NYM bestseller that is then compared with the waste before implementation to do the settings in the machine. Analysis to get the best quality on cable are rated based on a test of insulator using insulator tester and the conductor using the double bridge tester. From the results of the calculation of the optimum settings for it is known that machines with Speed settings pull 41 m/s Speed, Filling 33 m/s, and Speed Sheeting amounting to 29 m/s and the waste is reduced after implementation i.e. copper be 1458 Kg and PVC became 89,225 Kg in July 2016 which means tejadi decrease 41,375% in copper and 41,186% in PVC